Comparative analysis of catalyst operation in the process of higher paraffins dehydrogenation at different technological modes using mathematical model; Petroleum Science and Technology; Vol. 36, № 20 - Frantsina E. V. Evgeniya Vladimirovna; Ivanchina E. D. Emilia Dmitrievna; Ivashkina E. N. Elena Nikolaevna; Belinskaya N. S. Natalia Sergeevna; Fefelova K. O. Kseniya Olegovna (2018, 2018)
Title screen